Pemetaan Bibliometrik Literasi Keuangan, Literasi Fintech, dan Inklusi Keuangan dalam Penelitian Kinerja UKM - Sev Rahmiyanti; Suhatman Zaldi; Indradi Donny; Amrih Gilang Ganjar; Indra Jasmi (Universitas Serang Raya, 2025)
Abstract This study aims to map and analyze the development of the scientific literature related to financial literacy, fintech literacy, and financial inclusion in the context of the performance of Small and Medium Enterprises (SMEs) through a bibliometric analysis approach. This study used a quantitative-descriptive design with bibliographic data collected through the Publish or Perish software based on three main keywords, each resulting in 1,000 scientific articles. The collected data is then analyzed using VOSviewer to produce a citation network analysis map, publication trend analysis, and research density analysis. The results of the study show that there is a significant growth in publications and the formation of main thematic clusters that focus on financial literacy, fintech literacy, and financial inclusion as three interconnected pillars in the study of SME performance. Network analysis also shows a global pattern of collaboration between authors, institutions, and countries, with several dominant research centers. In addition, the mapping results reveal the inequality of research focus, where the integrative approach of the three concepts is still relatively limited. This study concludes that bibliometric analysis is able to provide a structural and systematic picture of the direction of scientific development, as well as become a conceptual basis for future empirical research. These findings contribute to strengthening the study of financial literacy and SMEs by providing a comprehensive and integrated scientific map. Keywords: financial literacy; fintech literacy; financial inclusion; SME performance; Bibliometric Analysis